Doppler Velocimetry of Uterine Artery in Bitches with Cystic Endometrial Hyperplasia-Pyometra Complex - K, Anusha; K, Sadasiva Rao; M, Srinivas; M, Sreenu; K, Aswani Kumar (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Doppler ultrasound is a useful diagnostic tool to evaluate uterine blood flow in different canine reproductive states. The aim of this study was to describe and compare uterine blood flow in bitches suffering from pyometra according to the ultrasonographic appearance of uterus. Seventy-five bitches with pyometra confirmed clinically, haematologically and ultrasonographically were included in the study. Ten healthy bitches with no haematological and ultrasonographic abnormality of uterus were also included in the study as control group. The bitches with pyometra were divided into four groups based on the sonographic characterization of uterus and its luminal contents, viz., B (few small cysts, normal endometrial surface, anechoic uterine content, n=11), C (many large cysts, irregular surface and hypertrophic endometrium, n=24), DH (many large cysts, irregular surface and hypertrophic endometrium, hyperechoic content, n=31) and DA (many large cysts, irregular surface and atrophic endometrium, hyperechoic content, n=9). The uterine horn diameter and uterine wall thickness was measured with two-dimensional ultrasonography. With the use of pulsed-wave Doppler, flow velocity waveforms of uterine artery were obtained. Parameters of blood flow velocity such as peak systolic velocity (PSV), end diastolic velocity (EDV), as well as haemodynamic parameters such as resistance index (RI), pulsatility index (PI) and systolic-diastolic ratio (S/D) were calculated electronically. Peak systolic velocity and end diastolic velocity were significantly higher in pyometra group than control with highest velocities recorded in DA group (P<0.05). The RI, PI and S/D were significantly lower in pyometra group than in control (P<0.05). The RI was significantly lower in group C and DA compared to groups B and DH (P<0.05). However, no significant difference was reported in PI and S/D among the groups of pyometra (P>0.05). It was concluded that the uterine artery blood flow velocity of bitches suffering from pyometra differs, not only from normal bitches, but also varies with the type of pyometra with varying pathological nature. Furthermore, haemodynamic parameters appear as useful markers to differentiate uterine pathologic conditions and to understand the pathological type of pyometra.